2016
DOI: 10.1039/c6tc03530b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism in 3d transition metal doped SnO

Abstract: Using first principles calculations, we investigate the structural and electronic properties of 3d transition metal doped SnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Similarly, a theoretical study on SnO bulk systems doped with a series of transition metals including Sc, V, Cr, Mn, Fe, Co, Ni, and Cu was also conducted. 45 Formation energies have been extensively calculated to predict the preferable doping sites, and the calculation results indicate that the doping sites can strongly influence the magnetic properties. For example, the spin polarization induced by transition-metal doping can be neutralized if two TM dopants are located closely.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a theoretical study on SnO bulk systems doped with a series of transition metals including Sc, V, Cr, Mn, Fe, Co, Ni, and Cu was also conducted. 45 Formation energies have been extensively calculated to predict the preferable doping sites, and the calculation results indicate that the doping sites can strongly influence the magnetic properties. For example, the spin polarization induced by transition-metal doping can be neutralized if two TM dopants are located closely.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, it is exceptional for V doping, which has a strong ferromagnetic behavior if the dopants are clustering and therefore is promising for the fabrication of magnetic semiconductors. 45 Although intensive research efforts have been devoted to bulk SnO, the report related to 2D SnO is very limited. The research interest was triggered by the stability of 2D SnO as a semiconductor with a band gap energy of ∼3.95 eV predicated with HSE06 functionals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Generally, spin polarization and magnetism can be induced in 2D semiconductors by different methods, such as surface defects, 15 transition metal atom doping, and adsorption. 16,17 However, these methods are difficult to be controlled precisely in experiment. Therefore, it is necessary to deposit SnO monolayers on magnetic substrates, which is expected to introduce spin polarization in the SnO monolayers by a magnetic proximity effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tao et al reported that B–, C–, N–, O–, and F-adsorption can tailor the magnetic and electronic properties of SnO monolayers . Generally, spin polarization and magnetism can be induced in 2D semiconductors by different methods, such as surface defects, transition metal atom doping, and adsorption. , However, these methods are difficult to be controlled precisely in experiment. Therefore, it is necessary to deposit SnO monolayers on magnetic substrates, which is expected to introduce spin polarization in the SnO monolayers by a magnetic proximity effect. , The magnetic proximity effect can effectively induce spin polarization in 2D monolayer semiconductors, such as WTe 2 /Fe 3 O 4 (111), graphene/Fe 4 N­(111), and MoS 2 /Fe 4 N­(111) heterostructures. Yang et al illustrated that graphene can strongly enhance the perpendicular magnetic anisotropy (PMA) of Co films, which indicates that the magnetic anisotropy energy (MAE) of 2D materials/ferromagnetic interfaces can be modulated. , In the magnetic proximity effect, the ferromagnetic substrate with large spin polarization and a high Curie temperature is important, where the cubic Fe 4 N has large spin polarization and a high Curie temperature of 760 K. , Moreover, a small lattice mismatch appears between the SnO monolayer and Fe 4 N­(001).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its potential application in spintronic devices, the ferromagnetism of SnO 2 has been investigated in both its undoped form and its doped form by transition metals. Obvious ferromagnetism has been observed at room temperature for both pristine SnO 2 films and nanocomposites, which is believed to stem from surface and lattice defects as well as from oxygen vacancies. Theoretical calculations further suggest that neutral cation vacancies induce ferromagnetism in SnO 2 . , Recently, the ferromagnetism of stannous oxide has also become of concern. SnO powder samples doped with Mn, Co, Ni, and other 3d transition metals, and hole-doped SnO monolayer, have been studied both experimentally and theoretically. To the best of our knowledge, however, there have not been any reports on the ferromagnetism of undoped SnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%